Perawatan Electro Motor Oil Max Pump pada Mesin Induk KM Dharma Kartika IX - Andi Hendrawan; Leonardus Heru Pratomo; Siswadi Hendrawan (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2021)
Problems that arise in the engine electro motor is mechanical damage that can be caused by many things such as mechanical damage, more current, low resistance low insulation and less lubrication, excess vibration and not draw, misalignment, natural aging process and factors due to the operating pattern of the induction motor, damage that occurs in the induction motor. Data is collected through Field Research, a direct review of the objects studied. Data collected through Observation (Direct Method) researchers make direct observations about objects studied on the SHIP KM. DHARMA KARTIKA IX. Must be done maintenance of electro motor components that is by checking the electro motor components and panels.